APLICAÇÃO DE REVESTIMENTOS COMESTÍVEIS NA QUALIDADE E CONSERVAÇÃO DE QUEIJO COALHO - Meira Júnior, Daniel Batista; De Sousa, Solange; Da Costa, Gilmar Freire (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2021)
The present work aimed to develop and apply edible coatings in "coalho" cheese and to evaluate the physical-chemical, microbiological and microscopic quality. The statistical design was completely randomized in a 5x4 factorial with 4 replicates, being 5 treatments: (control-cheese without coating, cheese coated with protein isolated from soybean + essential oil of basil, cassava starch + basil essential oil; isolated soy protein + chitosan and cassava starch + chitosan). The film-forming solutions were prepared and the cheeses were immersed for 30 seconds in the solutions. The storage period of the cheeses was 21 days under refrigeration conditions (5 ± 1 ° C,% 50 ± 2 RH). The physico-chemical and microbiological analyzes were performed at times 1, 7, 14 and 21 days. The results for pH and humidity did not present significant effect (p≤0.05) by Tukey's test. The result for thermotolerant coliforms was in compliance with the standards established by Brazilian legislation. In all treatments there was presence of coagulase positive Staphylococcus during storage. For Salmonella sp. Research, there was absence in 25 grams in all treatments. Edible films and coatings can improve shelf life and food quality, serving as a barrier to moisture transfer, better visual appearance, and reduced microbiological contamination.